Amoebic forms of Blastocystis spp. -evidence for a pathogenic role - Rajamanikam, A.; Govind, Suresh Kumar (BMC, 2013)
Background: Blastocystis spp. are one of the most prevalent parasites isolated from patients suffering from diarrhea, flatulence, constipation and vomiting. Itâs pathogenicity and pathophysiology remains controversial to date. Protease activity and amoebic forms have been reported previously in symptomatic isolates but there has been no conclusive evidence provided to correlate the protease activity and any specific life cycle stage of the parasite thus far. Methods: Symptomatic isolates with amoebic form were tested for protease activity and compared with symptomatic and asymptomatic isolates without amoebic form for 10 days culture period. Results: The present study demonstrates an elevated protease activity in cultures having a higher percentage of amoebic forms seen in symptomatic isolates. The growth curve demonstrated a significantly (p < 0.05) higher average number of parasite counts in asymptomatic compared to symptomatic isolates. Symptomatic isolates showed amoebic forms with percentages ranging from 5 to 17. Elevated protease activity was demonstrated in isolates that had higher percentages of amoebic forms with intense bands at higher molecular weight proteases (60 â 100 kDa). As days of culture proceeded, the protease quantification also showed a steady increase. Conclusion: This study elucidates a correlation between protease activity and percentage of amoebic forms. The finding implies that these forms could play a role in exacerbation of intestinal symptoms during Blastocystis spp. infection.